(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Tympanoplasty without mastoidectomy is performed to prevent recurrent infection and reconstruct the sound conducting mechanism. In our study 60 patients were selected for tympanoplasty operation. All operations were done in Dhaka National Medical college hospital and private hospital in Dhaka city. Choice of incision was post auricular approach. 20% of patients were operated under general anesthesia and 80% of patients were operated under local anesthesia. Age range of patient was between15 to 40 yrs. Female patients were predominant. Follow up of patients were up to 2yrs. Overall success rate was 93.3%. DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16015 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 14-16